Pengaruh Work-Life Balance, Salary Satisfaction, dan Leadership Terhadap Work Engagement Pegawai Sekda Kabupaten Sleman - Yasmine, Adelyn Chusna; Wahyuningsih, Tri Harsini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the effect of work-life balance, salary satisfaction, and leadership on the work engagement of employees of the Sekretariat Daerah Kabupaten Sleman. This research was conducted from December 2022 to January 2023 at the Sekretariat Daerah Kabupaten Sleman. The data were collected using a questionnaire. The population in this study were all PNS/ASN employees in the Sekretariat Daerah Kabupaten Sleman, totaling 159 employees, and the collection was carried out using a saturating sampling technique. The data analysis technique used is multiple linear regression. The results of this study indicate that work-life balance (X1) has no effect on work engagement (Y), salary satisfaction (X2) has no effect on work engagement (Y), and leadership (X3) has a positive and significant effect on work engagement (Y). Adjusted R Square value is 20.6%, means that 20.6% of work engagement variables can be explained by independent variables (work-life balance, salary satisfaction, and leadership), while the remaining 79.4% is explained by other variables not found in this study.